2019
DOI: 10.3747/co.26.4689
|View full text |Cite
|
Sign up to set email alerts
|

Patient Decision Aid for Contralateral Prophylactic Mastectomy for Use in the Consultation: A Feasibility Study

Abstract: Background Rates of contralateral prophylactic mastectomy (cpm) continue to rise internationally despite evidence-based guidance strongly discouraging its use in most women with unilateral breast cancer. The purpose of the present study was to develop and assess the feasibility of a knowledge translation tool [a patient decision aid (da)] designed to enhance evidence-informed shared decision-making about cpm.Methods A consultation da was developed using the Ottawa Patient Decision Aid Development eTraining in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…A large systematic review found that patient decision aids were associated with more accurate risk perceptions and improved decisional conflict scores [ 98 ]. In CPM decision-making, decision aids were acceptable and feasible to patients and healthcare professionals and associated with higher levels of knowledge [ 14 , 99 , 100 ]. An online interactive breast cancer in-visit decision aid (BIDA) has been used successfully by patients during breast surgery decision-making; under ‘Evaluation’, this tool showed published estimates using pictograms of 100 women for outcomes such as the risk of getting a new cancer in the other breast stratified by the three procedures—lumpectomy, unilateral mastectomy, and bilateral mastectomy—to compare those options [ 14 , 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large systematic review found that patient decision aids were associated with more accurate risk perceptions and improved decisional conflict scores [ 98 ]. In CPM decision-making, decision aids were acceptable and feasible to patients and healthcare professionals and associated with higher levels of knowledge [ 14 , 99 , 100 ]. An online interactive breast cancer in-visit decision aid (BIDA) has been used successfully by patients during breast surgery decision-making; under ‘Evaluation’, this tool showed published estimates using pictograms of 100 women for outcomes such as the risk of getting a new cancer in the other breast stratified by the three procedures—lumpectomy, unilateral mastectomy, and bilateral mastectomy—to compare those options [ 14 , 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…We included a final sample of 54 articles in the comparison of analyst and author ratings (Appendix Figure 1). Appendix Table 1 contains a list of the articles included in the final sample, 26-91 .…”
Section: Methodsmentioning
confidence: 99%
“…Women in our study, whether they underwent cpm or not, believed that bilateral mastectomy would improve reconstruction outcomes 34 . One way to address fear, anxiety, and esthetic concerns on the part of patients is to develop educational materials such as patient decision aids that accurately inform patients about the risks of contralateral bca and of future recurrence, the lack of a survival benefit for cpm, the psychosocial ramifications of cpm, and the outcomes of reconstruction, including its risks and benefits 35 . Other strategies to address the core theme of fear and anxiety among women with bca, which centres on cancer recurrence in the contralateral breast, could involve the use of social and other media to educate the public about the actual risks and options.…”
Section: Patient Fear and Anxiety Esthetic Concernsmentioning
confidence: 99%